2014
DOI: 10.14356/kona.2014018
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Processing of Graphene and Its Application to Oil Absorbent and Glucose Biosensor

Abstract: Graphene (GR) is a flat monolayer of sp 2 -bonded single carbon atoms densely packed into a honeycomb crystal lattice. Due to its unique characteristics, GR is expected to contribute to enhanced nano-electronic, bio-electronic devices, etc. in the near future. However, the single-layered GR sheets have a tendency to form irreversible aggregates or even to restack easily due to strong attraction between sheets. Preventing of aggregation and restacking of GR is achieved by the dimensional transition from flat sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…GO sheets in the colloidal solution were exfoliated by ultrasonic treatment for 1 h 20 min before the aerosol spray pyrolysis process. A description of the experimental procedure used for the aerosol process is available in the literature . The droplets of the colloidal solution generated by an ultrasonic atomizer were carried by argon 1.0 L/min into a pretreated tubular furnace (1073 K).…”
Section: Methodsmentioning
confidence: 99%
“…GO sheets in the colloidal solution were exfoliated by ultrasonic treatment for 1 h 20 min before the aerosol spray pyrolysis process. A description of the experimental procedure used for the aerosol process is available in the literature . The droplets of the colloidal solution generated by an ultrasonic atomizer were carried by argon 1.0 L/min into a pretreated tubular furnace (1073 K).…”
Section: Methodsmentioning
confidence: 99%
“…Materials being explored for non-enzymatic amperometric sensors include metals, metal oxides, complexes, and carbon nanomaterials [63]. Kim et al explored the role of graphene and reviewed its application as a glucose biosensor [64]. More recently, the same group synthesized silver-graphene-titanium dioxide nanocomposites used as a glucose biosensor [65].…”
Section: Nanoparticles Of Biomedical Importancementioning
confidence: 99%
“…In our earlier works [22][23][24][25][26][27], it was demonstrated that GRbased composites with a three-dimensional (3D) morphology had a high free volume and compressive strength [22,24,27]. In addition, they could be tightly packed without significantly decreasing the accessible surface area, unlike the 2D GRbased sheets [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they could be tightly packed without significantly decreasing the accessible surface area, unlike the 2D GRbased sheets [25][26][27]. The fabricated 3D GR-based composites could also deliver significantly higher electron transfers and electrical conductivity in the electrocatalyst performance [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation